Does Intraneuronal Accumulation of Carboxyl-terminal Fragments of the Amyloid Precursor Protein Trigger Early Neurotoxicity in Alzheimer’s Disease? - Lauritzen, I.; Pardossi-Piquard, R.; Bourgeois, A.; Bécot, A.; Checler, F. (Current Alzheimer Research, 2019)
Background: Alzheimer’s disease (AD) is associated with extracellular accumulation and aggregation of amyloid β (Aβ) peptides ultimately seeding in senile plaques. Recent data show that their direct precursor C99 (βCTF) also accumulates in AD-affected brain as well as in AD-like mouse models. C99 is consistently detected much earlier than Aβ, suggesting that this metabolite could be an early contributor to AD pathology. C99 accumulates principally within endolysosomal and autophagic structures and its accumulation was described as both a consequence and one of the causes of endolysosomalautophagic pathology, the occurrence of which has been documented as an early defect in AD. C99 was also accompanied by C99-derived C83 (αCTF) accumulation occurring within the same intracellular organelles. Both these CTFs were found to dimerize leading to the generation of higher molecular weight CTFs, which were immunohistochemically characterized in situ by means of aggregate-specific antibodies. Discussion: Here, we discuss studies demonstrating a direct link between the accumulation of C99 and C99-derived APP-CTFs and early neurotoxicity. We discuss the role of C99 in endosomal-lysosomalautophagic dysfunction, neuroinflammation, early brain network alterations and synaptic dysfunction as well as in memory-related behavioral alterations, in triple transgenic mice as well as in newly developed AD animal models. Conclusion: This review summarizes current evidence suggesting a potential role of the β -secretasederived APP C-terminal fragment C99 in Alzheimer’s disease etiology.
Keywords: synaptic defects